Study of Bakamla RI Building Policy in Order to Implement Maritime Security Enforcer’s Tasks Based on Potential Capability - Sudiro, Pratondo Ario Seno; Firdaus, Elsa Aliya Rizqoh (Journal of Strategic and Global Studies, 2023)
Maritime Security is defined as secure and controlled sea by means of free from violation, pollution, and lawbreaking threats. There are several ‘red zone’ areas in Indonesian sea region which contain several kinds of threat. The existence of ‘red zone’ areas shows that Maritime Security in Indonesian sea region hasn’t been realized yet. Law No. 32 of 2014 mentioned Bakamla RI as Maritime Security enforcer in Indonesian sea region. Bakamla RI is Maritime Security enforcer whose task is to enforce nation sovereignty and maritime law except direct invasion. The purpose of this research is building Bakamla RI to implement Maritime Security based on its capability. Its focus will be divided into two parts: internal (focus on Bakamla RI’s functions under law) and external (focus on procurement of the equipment from national industries). This research uses Qualitative Method processing major information from literature observation at the legislation mainly Law No. 32 of 2014 that supported by some articles from scientific journals and handbooks and minor information from policy brief or strategical planning brief and direct statement from live meeting were also used. It results two potential capabilities of Bakamla RI to be considered during the study of Bakamla RI’s building policy. First is Bakamla RI’s functions as Maritime Security enforcer and second is Bakamla RI’s equipment that available to be procured. The capabilities implicate two main policies in order to build Bakamla RI as Maritime Security enforcer. First is determination of Maritime Zone Region and second is integration of all support equipment in each Maritime Zone Region.